Corpus Callosum Anomalies: Prenatal Diagnosis, Genetic Findings, and Perinatal Outcomes - Arslanoğlu, Tuğçe; Uludağ, Sezin; Açar, Deniz Kanber; Ateş Aydın, Alev (The European Research Journal, 2026)
Objectives: The aim of this study was to evaluate the subtype distribution of prenatally diagnosed corpus callosum (CC) anomalies. We also assessed associated central nervous system (CNS) and extracranial anomalies, genetic findings, perinatal outcomes, and the contribution of ultrasonography and fetal MRI to prenatal diagnosis. Methods: This retrospective, single-center study was conducted in a tertiary perinatology clinic between 2016 and 2025. A total of 124 fetuses with prenatally diagnosed CC anomalies were included. Diagnosis was based on obstetric ultrasound, and fetal magnetic resonance imaging (MRI) was performed when ultrasound findings were inconclusive. Cases were classified by subtype, and associated CNS or extracranial anomalies, genetic test results, and pregnancy outcomes were recorded. Results: The study included 124 fetuses diagnosed with CC anomalies during the prenatal period. The mean gestational age at diagnosis was 26.6±4.7 weeks. Pregnancy resulted in termination in 67.7% of cases and live birth in 32.3%. In cases that ended in termination, diagnosis and delivery occurred at earlier gestational weeks, and birth weights were lower. Additional anomalies were present in 42.7% of cases, most commonly involving the central nervous system and the heart. Complete CC agenesis was the most frequent subtype (54%). Genetic testing was more often performed in the termination group and identified chromosomal abnormalities such as trisomy 18, trisomy 13, and 22q11 deletion. Fetal MRI was performed in 45 cases, confirming the ultrasound diagnosis in 36 and leading to diagnostic revision in 9 cases. Conclusions: This study summarizes our experience in the evaluation of pregnancies diagnosed with CC anomalies. In our cohort, prognosis was mainly influenced by whether the anomaly was isolated, along with fetal MRI and genetic test findings. Overall, our approach was similar to that reported in the literature. Nevertheless, each case required individual assessment, and counseling was adjusted according to the clinical findings.